Effect of residual fertilizer on green corn yield in rotation with potato crop - Silva, Ernani Clarete da; Filho, Ademar Virgolino da Silva; Alvarenga, Marco Antonio Rezende (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out at Epamig, Estação Experimental de Três Pontas, MG, Brazil, to evaluate the residual effect of fertilizer applied in potatoes (Solanum tuberosum L.) field on successive green corn (Zea mays L.) production. The potato cv. Achat was grown in plots with three treatments: 0, 2 and 4 t ha-1 of NPK 4-16-8 fertilizer. After potato harvest, hybrid AG-162 Agroceres corn was sown in a randomized block experimental design in split plots, namely: in the plots, the potato fertilizer; and in the subplots, the green corn fertilizer, one with, and one without base fertilizer, and four replications. The following characteristics were evaluated: average length of plant, number of ears per plot, ear production, and soil concentration of P, K+, Ca2+ and Mg2+. The increase of mineral fertilization to the potato crop favored a greater nutrients' residual effect, mainly soil exchangeable P, K and Ca, which may increase green corn yield when in rotation with potato crop.